Corrosion resistance enhancement of magnesium alloy by N-doped graphene quantum dots and polymethyltrimethoxysilane composite coating. (February 2020) - Jiang, B.K.; Chen, A.Y.; Gu, J.F.; Fan, J.T.; Liu, Y.; Wang, P.; Li, H.J.; Sun, H.; Yang, J.H.; Wang, X.Y.
Abstract: A composite coating of N-doped graphene quantum dots (N-GQDs)/polymethyltrimethoxysilane (PMTMS) is prepared on the surface of AZ91D magnesium alloy via electrodeposition and subsequent silane treatment. The microstructure of the N-GQDs/PMTMS composite coating is characterized by field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The corrosion resistance performance is investigated by electrochemical impedance spectroscopy (EIS) and immersion test in NaCl solution (3.5 wt%). The N-GQDs/PMTMS composite coating exhibits a significant enhancement of corrosion resistance due to the chemical bonding of N-GQDs coating with Mg substrate and PMTMS coating. The formation mechanisms and nature of the corrosion resistance of the N-GQDs/PMTMS coating are discussed. Graphical abstract: Image 1